THU0620 On demand use of anakinra for the attacks of familial mediterranean fever (FMF). (12th June 2018) - Babaoglu, H.; Varan, O.; Kucuk, H.; Atas, N.; Satis, H.; Salman, R.B.; Ozturk, M.A.; Goker, B.; Haznedaroglu, S.; Tufan, A.
Abstract : Background: IL-1 blocking agents have been shown to be effective in the prevention of attacks in colchicine-resistant FMF (crFMF) patients by their regular use. However, their high cost, side effects and treatment incompliance limit their use which might be overwhelmed by on-demand use of them which has not been reported in FMF patients. Herein, we evaluated the efficacy of on demand use of anakinra in crFMF patients. Methods: Data were derived from Gazi FMF cohort which was established in the year 2010. From that date patients with FMF who were diagnosed according to the Tel Hashomer criteria were registered. Co-morbidities, detailed attack characteristics, type, duration, severity, treatments, laboratory parameters and impact of FMF on their life in terms of quality of life and work productivity were recorded either by FMF diary or a mobile phone application (FMF AIDD free to download from AppStore and Android market). A retrospective cohort analysis was made from records of patients who have ever been treated with IL-1 inhibitors. Results: A total of 60 patients were treated with anakinra in our cohort and 15 patients were identified who were received on demand anakinra protocol. Rationale for on demand use of anakinra was prominent prodrome or trigger for attacks and patients' personal claim. Six patients were switched from regular use and 9 were directly started as on demand use. All were using background colchicine in maximum tolerated doses. None of patients had evidence of persistently elevated acute phase reactants or proteinuria. The median duration of on demand anakinra use was 6 (min 3- max 36) months. Pre- and post- on demand anakinra periods were compared (table 1). Patient reported attack severity (p=0.002), duration (p=0.001), absenteeism (p=0.001) and presenteeism (p=0.002) were significantly improved but C-reactive protein (CRP) remained in the same levels. On demand anakinra prevented progression of prodromes to full-blown attacks which was demonstrated by decrease in the rate of attack/prodrome ratio (p=0.002). On demand anakinra can be continued in 10 subjects on long-term but continuous treatment was required in 5 subjects. Attack frequency and work productivity parameters are adjusted for 3 months intervals. VAS: visual analogue scale, CRP: C-reactive protein, AIDAI: autoinflammatory disease activity index Conclusions: On demand anakinra significantly improved FMF attacks which suggest this approach would be of benefit in daily practice in selected patients. Disclosure of Interest: None declared